Monoketone Curcuminoids: An Updated Review of Their Synthesis and Biological Activities - Tatiana M. Vieira; Lívia S. Tanajura; Vladimir C. G. Heleno; Lizandra G. Magalhães; Antônio E. M. Crotti (MDPI AG, 2024)
Curcumin (or diferuloylmethane), a component of Curcuma longa L. rhizomes, displays various biological and pharmacological activities. However, it is poorly bioavailable and unstable in physiological pH. In this review, we cover papers published between 2019 and 2023 on the synthesis and biological activities of more stable and effective curcumin analogs known as monoketone curcuminoids (MKCs) or "monocarbonyl curcuminoids." Recent advances in Claisen-Schmidt condensation, the standard procedure to synthesize MKCs, including the use of ionic liquids, are addressed. MKCs' antimicrobial, anticancer, antioxidant, and antiparasitic actions, as well as other less common MKC biological and pharmacological activities, have been shown to be similar or higher than curcumin. The promising biological and pharmacological activities, combined with the attractive synthetic aspects (e.g., good yields and an easiness of product isolation) to obtain MKCs, make this class of compounds an interesting prospect for further antimicrobial, anticancer, and antiparasitic drug discovery.